Drought-induced tree species replacement is reflected in the spatial variability of soil respiration in a mixed Mediterranean forest - Barba, Josep; Yuste, Jorge Curiel; Martínez-Vilalta, Jordi; Lloret, Francisco (Forest Ecology and Management, 2013)
As episodes of drought-induced forest mortality are being increasingly reported worldwide and may become more frequent in the future as a result of climate change, it is essential to characterize their functional implications in terms of ecosystem carbon and water fluxes. We investigated the spatial variability of soil respiration in a mixed Mediterranean forest located on rugged terrain, where Scots pine (Pinus sylvestris) is affected by drought-induced dieback and appears to have been replaced by Holm oak (Quercus ilex) as the dominant tree species. Soil respiration was measured in spring 2010 on two plots (16.2 × 16.2 m) using a static closed chamber method (soda lime technique) and a systematic sampling (1.8-m grid) including 100 points per plot. Biotic and abiotic variables, such as soil moisture, soil temperature, soil organic matter content, stoniness, pH, fine root C:N ratio and biomass, tree basal area and tree species and health condition of nearest neighbouring tree were also recorded. Our results showed that the spatial variability of soil respiration under optimal environmental conditions (spring) was high and showed no spatial autocorrelation on the scale studied (1–18 m). A mixed-effects model applied to explain the spatial variability of soil respiration indicated that only the variables related to forest structure (i.e., health condition and basal area) explained any of the observed variability of soil respiration (R2 = 0.45). Our model revealed that soil respiration was highest in soils close to dead pines and under Holm oak trees, suggesting that tree mortality and species replacement of pine trees by Holm oak may lead to higher soil respiration fluxes. The direct effect of tree mortality on soil respiration may be a transitory response caused by fine root mortality. Furthermore, the fact that tree species replacement as a result of drought-induced die-off is accompanied by concomitant changes in soil respiration has important implications for soil and ecosystem carbon balance
Keywords: Forest dieback; Mediterranean ecosystem; Pinus sylvestris; Quercus ilex; Soil CO2 efflux; Spatial variability

Effect of wildfires on soil respiration in three typical Mediterranean forest ecosystems in Madrid, Spain - Uribe, C; Inclán, R; Sanchez, D M; Clavero, M A; Fernandez, A M; Morante, R; Cardena, A; Blanco, A; Van Miegroet, H (PLANT AND SOIL, 2013)
Mediterranean forests are vulnerable to numerous threats including wildfires due to a combination of climatic factors and increased urbanization. In addition, increased temperatures and summer drought lead to increased risk of forest fires as a result of climate change. This may have important consequences for C dynamics and balance in these ecosystems. Soil respiration was measured over 2 successive years in Holm oak (Quercus ilex subsp. ballota; Qi); Pyrenean Oak (Quercus pyrenaica Willd; Qp); and Scots pine (Pinus sylvestris L.; Ps) forest stands located in the area surrounding Madrid (Spain), to assess the long term effects of wildfires on C efflux from the soil, soil properties, and the role of soil temperature and soil moisture in the variation of soil respiration. Soil respiration, soil temperature, soil moisture, fine root mass, microbial biomass, biological and chemical soil parameters were compared between non burned (NB) and burned sites (B). The annual C losses through soil respiration from NB sites in Qi, Qp and Ps were 790, 1010, 1380 gCm(-2) yr(-1), respectively, with the B sites emitting 43 %, 22 % and 11 % less in Qi, Qp and Ps respectively. Soil microclimate changed with higher soil temperature and lower soil moisture in B sites after fire. Exchangeable cations and the pH also decreased. The total SOC stocks were not significantly altered, but 6-8 years after wildfires, there was still measurably lower fine root and microbial biomass, while SOC quality changed, indicated by lower the C/N ratio and the labile carbon and a relative increase in refractory SOC forms, which resulted in lower Q(10) values. We found long term effects of wildfires on the physical, chemical and biological soil characteristics, which in turn affected soil respiration. The response of soil respiration to temperature was controlled by moisture and changed with ecosystem type, season, and between B and NB sites. Lower post-burn Q(10) integrated the loss of roots and microbial biomass, change in SOC quality and a decrease in soil moisture.
Keywords: climate change; Pinus sylvestris; Quercus ilex; Quercus pyrenaica; soil parameters; Soil respiration; wildfires

Climate change impacts on tree ranges: model intercomparison facilitates understanding and quantification of uncertainty - Cheaib, Alissar; Badeau, Vincent; Boe, Julien; Chuine, Isabelle; Delire, Christine; Dufrêne, Eric; François, Christophe; GRITTI, EMMANUEL S; Legay, Myriam; Pagé, Christian; Thuiller, Wilfried; Viovy, Nicolas; et al. (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Model-based projections of shifts in tree species range due to climate change are becoming an important decision support tool for forest management. However, poorly evaluated sources of uncertainty require more scrutiny before relying heavily on models for decision-making. We evaluated uncertainty arising from differences in model formulations of tree response to climate change based on a rigorous intercomparison of projections of tree distributions in France. We compared eight models ranging from niche-based to process-based models. On average, models project large range contractions of temperate tree species in lowlands due to climate change. There was substantial disagreement between models for temperate broadleaf deciduous tree species, but differences in the capacity of models to account for rising CO2 impacts explained much of the disagreement. There was good quantitative agreement among models concerning the range contractions for Scots pine. For the dominant Mediterranean tree species, Holm oak, all models foresee substantial range expansion.
Keywords: climate change; Fagus sylvatica; France; Pinus sylvestris; Quercus ilex; Quercus petraea; Quercus robur; species range; vegetation model intercomparison

Seedling emergence and growth of Quercus spp. following severe drought effects on a Pinus sylvestris canopy - Galiano, Lucía; Martínez-Vilalta, Jordi; Eugenio, Màrcia; Granzow-de la Cerda, Íñigo; Lloret, Francisco (Journal of Vegetation Science, 2012)
Questions We addressed the following questions: (1) did defoliation and die-off of the dominant Pinus sylvestris, induced by an extreme drought episode, favour emergence of other tree species; (2) did the defoliated canopies of P. sylvestris resulting from drought promote radial growth among other pre-existing tree species seedlings under them? Location P. sylvestris forest in Central Pyrenees (NE Spain) affected by a severe drought in 2004–2005. Methods Despite increased focus on climate-related forest die-off, studies of the effects on regeneration processes following extreme drought remain scarce. We analysed whether an episode of drought-induced mortality on the dominant P. sylvestris L. may act as a driver of vegetation shift. Seedlings of Quercus humilis Mill. and Q. ilex L. from 27 plots were sampled under P. sylvestris canopies with <50% and ≥50% defoliation (standing dead trees included) to determine age distribution and radial growth using a retrospective, dendrochronological approach. Results Drought-induced canopy losses appear not to be compensated by regeneration of P. sylvestris. Recruitment of below-canopy tree species (specifically Q. humilis and Q. ilex) that could potentially become dominant was high in the entire studied area. However, the spatial patterns of Quercus spp. regeneration following the 2004–2005 drought were complex. While the emergence of new Quercus spp. seedlings was reduced under open, drought-induced canopies, growth of seedlings already established was favoured in open-canopy conditions. Conclusions Although the effects of extreme drought events may disfavour the establishment of new recruits, enhanced growth responses of a pre-established seedling bank could still contribute to accelerate forest dynamics under drier conditions. Because of the predicted increases in intensity and frequency of extreme droughts, monitoring studies are key to elucidate whether the initial patterns observed will be maintained in the long term, eventually leading to a vegetation shift.
Keywords: Canopy gap; Extreme climatic episode; Pinus sylvestris; Quercus humilis; Quercus ilex; seedling growth; Seedling recruitment; tree mortality; Vegetation shift

Predicting the future of forests in the Mediterranean under climate change, with niche- and process-based models: CO2 matters! - KEENAN, Trevor; Maria Serra, JOSEP; Lloret, Francisco; Ninyerola, Miquel; SABATE, Santiago (Global Change Biology, 2011)
Assessing the potential future of current forest stands is a key to design conservation strategies and understanding potential future impacts to ecosystem service supplies. This is particularly true in the Mediterranean basin, where important future climatic changes are expected. Here, we assess and compare two commonly used modeling approaches (niche- and process-based models) to project the future of current stands of three forest species with contrasting distributions, using regionalized climate for continental Spain. Results highlight variability in model ability to estimate current distributions, and the inherent large uncertainty involved in making projections into the future. CO2 fertilization through projected increased atmospheric CO2 concentrations is shown to increase forest productivity in the mechanistic process-based model (despite increased drought stress) by up to three times that of the non-CO2 fertilization scenario by the period 2050–2080, which is in stark contrast to projections of reduced habitat suitability from the niche-based models by the same period. This highlights the importance of introducing aspects of plant biogeochemistry into current niche-based models for a realistic projection of future species distributions. We conclude that the future of current Mediterranean forest stands is highly uncertain and suggest that a new synergy between niche- and process-based models is urgently needed in order to improve our predictive ability.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 6 may 2010; april 2010 and accepted; BIOMOD; co 2 fertilization; CO2 fertilization; Drought; gotilwa 1; GOTILWA+; niche-based models; Pinus halepensis; Pinus sylvestris; Quercus ilex; received 19 january 2010; revised version received 27; Species distribution

N2O and CH4 fluxes in undisturbed and burned holm oak, scots pine and pyrenean oak forests in central Spain - Inclán, Rosa; Uribe, Carla; Sánchez, Laura; Sánchez, Dolores M.; Clavero, Ángeles; Fernández, Ana María; Morante, Ramón; Blanco, Alfredo; Jandl, Robert (Biogeochemistry, 2010)
We investigated N2O and CH4 ﬂuxes from soils of Quercus ilex, Quercus pyrenaica and Pinus sylvestris stands located in the surrounding area of Madrid (Spain). The ﬂuxes were measured for 18 months from both mature stands and post ﬁre stands using the static chamber technique. Simultaneously with gas ﬂuxes, soil temperature, soil water content, soil C and soil N were measured in the stands. Nitrous oxide ﬂuxes ranged from -11.43 to 8.34 lg N2O–N m -2 h -1 in Q.ilex, -7.74 to 13.52 lg N2O–N m -2 h -1 in Q. pyrenaica and -28.17 to 21.89 lg N2O–N m -2 h -1 in P. sylvestris. Fluxes of CH4 ranged from -8.12 to 4.11 lg CH4– C m -2 h -1 in Q.ilex, -7.74 to 3.0 lg CH4 –C m -2 h -1 in Q. pyrenaica and -24.46 to 6.07 lg CH4–C m -2 h -1 in P. sylvestris. Seasonal differences were detected; N2O ﬂuxes being higher in wet months whereas N2O ﬂuxes declined in dry months. Net consumption of N2O was related to low N availability, high soil C contents, high soil temperatures and low moisture content. Fire decreased N2O ﬂuxes in spring. N2O emissions were closely correlated with previous day’s rainfall and soil moisture. Our ecosystems generally were a sink for methane in the dry season and a source of CH4 during wet months. The available water in the soil inﬂuenced the observed seasonal trend. The burned sites showed higher CH4 oxidation rates in Q. ilex, and lower rates in P. sylvestris. Overall, the data suggest that ﬁre alters both N2O and CH4 ﬂuxes. However, the magnitude of such variation depends on the site, soil characteristics and seasonal climatic conditions.
Keywords: á; fire; greenhouse flux á fire; Greenhouse ﬂux; Pinus sylvestris; Quercus ilex; Quercus pyrenaica; quercus pyrenaica á pinus; Soil temperature; soil temperature á; Soil water content; soil water content á; sylvestris á

Effects of environmental stress on forest crown condition in Europe. Part IV: statistical analysis of relationships - Klap, J M; Voshaar, J H Oude (Water, Air, & Soil …, 2000)
Site-speciﬁc estimates for various environmental stress factors were related with measured crown condition data at a systematic 16 16 km2 grid over Europe, according to previously stated hypotheses, using a multiple regression approach, including interactions, and lagged effects of stress factors. Methodological differences among countries accounted for >30% of the variation in defoliation. Nevertheless, crown condition was found to vary naturally with tree age, altitude, drought stress and, most likely, also pathogenic fungi and insects. Signiﬁcant impacts of air pollution (speciﬁcally ozone but also NOx , SOx and acid deposition) were found at regional levels in parts of central Europe, particularly for deciduous species. Impacts seemed less signiﬁcant for conifers, especially for spruce, but this might be affected by confounding effects or strong correlations between (a harsh) climate and (low) atmospheric deposition in the area where spruce predominates. National studies indicate that ozone and acid deposition can have a signiﬁcant effect on the defoliation of spruce as well. We conclude that while forest condition varies naturally, continued emissions will contribute further to forest decline in the long term.
Keywords: acid deposition; air pollution; correlative study; critical load; defoliation; Fagus sylvatica; forest vitality; meteorological stress; picea abies; Pinus sylvestris; Quercus ilex; Quercus petraea; Quercus robur